2018
DOI: 10.1002/lt.25035
|View full text |Cite
|
Sign up to set email alerts
|

Higher retransplantation rate following extended right split‐liver transplantation: An analysis from the eurotransplant liver follow‐up registry

Abstract: We read with interest the article by Andrassy et al. in Liver Transplantation on the Eurotransplant experience with extended right graft (ERG) split-liver transplantation (SLT). (1) In that series, an ex situ split was usually performed in pediatric centers, shipping ERGs to adult centers, resulting in prolonged cold ischemia time (CIT), which is identified as a significant risk factor for graft failure. These results suggested reconsidering what is the best SLT allocation policy.The Italian SLT experience sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…In one study, recipients of left‐lateral splits (segments 2 and 3) had better outcomes than patients who had received right‐extended lobes (segments 1 and 4‐8) or full‐right (segments 5‐8) or full‐left (segments 1‐4) splits . A retrospective study that compared WLT to the transplantation of right‐extended lobes showed similar survival rates, although the latter were linked to a higher risk for retransplantation . In contrast, recipients of full‐left splits showed more complications in a study that compared full‐left and full‐right SLT …”
Section: Results: Comparability Of Outcomes Of Slt and Wltmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, recipients of left‐lateral splits (segments 2 and 3) had better outcomes than patients who had received right‐extended lobes (segments 1 and 4‐8) or full‐right (segments 5‐8) or full‐left (segments 1‐4) splits . A retrospective study that compared WLT to the transplantation of right‐extended lobes showed similar survival rates, although the latter were linked to a higher risk for retransplantation . In contrast, recipients of full‐left splits showed more complications in a study that compared full‐left and full‐right SLT …”
Section: Results: Comparability Of Outcomes Of Slt and Wltmentioning
confidence: 99%
“…Specific split liver programs, for example, in northern Italy, have shown that a split liver rate of more than 20% can be achieved . Following these positive results, Italy has opted for a national policy that demands that every liver from adult donors aged ≥50 years is to be evaluated for SLT …”
Section: Ethical Discussionmentioning
confidence: 99%
See 2 more Smart Citations